Icariside II Effectively Reduces Spatial Learning and Memory Impairments in Alzheimer’s Disease Model Mice Targeting Beta-Amyloid Production - Yan, Lingli; Deng, Yuanyuan; Gao, Jianmei; Liu, Yuangui; Li, Fei; Shi, Jingshan; Gong, Qihai (Frontiers in Pharmacology, 2017)
Icariside II (ICS II) is a broad-spectrum anti-cancer natural compound extracted from Herba Epimedii Maxim. Recently, the role of ICS II has been investigated in central nervous system, especially have a neuroprotective effect in Alzheimer’s disease (AD). In this study, we attempted to investigate the effects of ICS II, on cognitive deficits and beta-amyloid (Aβ) production in APPswe/PS1dE9 (APP/PS1) double transgenic mice. It was found that chronic ICS II administrated not only effectively ameliorated cognitive function deficits, but also inhibited neuronal degeneration and reduced the formation of plaque burden. ICS II significantly suppressed Aβ production via promoting non-amyloidogenic APP cleavage process by up-regulating a disintegrin and metalloproteinase domain 10 (ADAM10) expression, inhibited amyloidogenic APP processing pathway by down-regulating amyloid precursor protein (APP) and β-site amyloid precursor protein cleavage enzyme 1 (BACE1) expression in APP/PS1 transgenic mice. Meanwhile, ICS II attenuated peroxisome proliferator-activated receptor-γ (PPARγ) degradation as well as inhibition of eukaryotic initiation factor α phosphorylation (p-eIF2α) and PKR endoplasmic reticulum regulating kinase phosphorylation (p-PERK). Moreover, phosphodiesterase type 5 inhibitors (PDE5-Is) have recently emerged as a possible therapeutic target for cognitive enhancement via inhibiting Aβ levels, and we also found that ICS II markedly decreased phosphodiesterase-5A (PDE5A) expression. In conclusion, the present study demonstrates that ICS II could attenuate spatial learning and memory impairments in APP/PS1 transgenic mice. This protection appears to be due to the increased ADAM10 expression and decreased expression of both APP and BACE1, resulting in inhibition of Aβ production in the hippocampus and cortex. Inhibition of PPARγ degradation and PERK/eIF2α phosphorylation are involved in the course, therefore suggesting that ICS II might be a promising potential compound for the treatment of AD.